Vagus nerve stimulation attenuates septic shock-induced cardiac injury in rats - Chen, Y; Cui, M; Cui, Y (Physiological research, 2023)
This research aimed to evaluate whether vagus nerve stimulation (VNS) could effectively prevent septic shock-induced cardiac injury in rats and investigate the potential mechanisms. Female Sprague-Dawley rats were divided into the Sham group (sham cecal ligation and puncture [CLP] plus vagal nerve trunk separation), the Vehicle group (CLP plus vagal nerve trunk separation), and the VNS groups (CLP plus vagal nerve trunk separation plus VNS). The left ventricular function was analyzed by echocardiography. Histologic examinations of the cardiac tissues were performed through hematoxylin and eosin staining and TUNEL staining. The Vehicle group had worse cardiac function, higher levels of cardiac injury markers, and enhanced myocardial apoptosis than the Sham group. The rats in the VNS groups had enhanced cardiac function, lower levels of cardiac injury markers, and inhibited myocardial apoptosis than those in the Vehicle group. Elevated interleukin-1beta and tumor necrosis factor-alpha-levels and activated nuclear factor kappa B (NF-kappa-B) signal in septic shock rats were inhibited by the performance of VNS. This study suggests that VNS contributes to the reduction of myocardial apoptosis and improvement of left ventricular function to attenuate septic shock-induced cardiac injury in rats. The performance of VNS inhibits the inflammatory responses in heart tissues via the regulation of NF-kappa-B signal.
Keywords: Vagus Nerve Stimulation; Animals; Heart; Female; Heart Injuries; ženské pohlaví; srdce; Shock, Septic; Rats, Sprague-Dawley; vagová stimulace; septický šok; potkani Sprague-Dawley; poranění srdce; krysa rodu Rattus; NF-kappa B; zvířata; Myocardium; myokard; Rats